2018
DOI: 10.3390/ijerph15102158
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Capacity for Sperm Production Induced by Perinatal Bisphenol A Exposure Is Associated with an Increased Inflammatory Response in the Offspring of C57BL/6 Male Mice

Abstract: Many previous studies have indicated the adverse effects of bisphenol A (BPA) on sperm production and quality; however, the mechanisms underlying BPA male reproductive toxicity have yet to be elucidated. The main purpose of this study was to investigate the effect of perinatal exposure to BPA on the spermatogenic capacity of male offspring, and to explore the possible influence of inflammatory responses in BPA reproductive toxicity. Twenty-one pregnant C57BL/6mice were randomly divided into three groups: a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Our data suggested that LYC is beneficial for decreasing of the levels of nuclear damage to DNA and deformity rate and increasing the values of sperm motility, number, and density induced by DEHP. A study showed that the decreasing capacity of spermatogenesis in male offspring might be associated with the AHR signaling pathways in the testes . It has been reported that AHR overexpression was found in Sertoli, Leydig, and spermatid cells of infertile subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that LYC is beneficial for decreasing of the levels of nuclear damage to DNA and deformity rate and increasing the values of sperm motility, number, and density induced by DEHP. A study showed that the decreasing capacity of spermatogenesis in male offspring might be associated with the AHR signaling pathways in the testes . It has been reported that AHR overexpression was found in Sertoli, Leydig, and spermatid cells of infertile subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, during lactation, prolonged exposure to water contaminated with 0.2 or 2 µg/mL of BPA was not associated with any changes in epididymal or testicular volume compared with the control group. However, the male offspring of dams exposed to 2 µg/mL BPA showed reduced testosterone and sperm concentration and an increase in abnormal cells compared with controls [61]. Another interesting result from this study was the finding of a change in the inflammatory pathways in the groups exposed to the highest dose of BPA (increase in TNFα and higher NFkB and TLR4 protein expression).…”
Section: Postnatal Exposure: Are There Repercussions For Adult Testicmentioning
confidence: 52%
“…Furthermore, the BPA concentration in PM 2.5 of the C 3 is slightly higher than that in the PM 10 fraction with 24.9 µg/mg. In animal studies, doses in the low µg/kg body weight (BW) range already showed significant effects on the reproduction system and allergic asthmatic responses (Meng et al 2018;Yanagisawa et al 2019). Exposure rates per cm 3 cut material can be calculated according to the formula with ER = exposure rate in µg/(min × kg BW × cm 3 cut material), BW = body weight in kg, BPA conc.…”
Section: Bpa and Pahs Quantificationmentioning
confidence: 99%